Sex-dependent association analysis between serum uric acid and spontaneous hemorrhagic transformation in patients with ischemic stroke - Tang, Ye; Liu, Ming-Su; Fu, Chong; Li, Guang-Qin (Frontiers in Neurology, 2023)
Abstract Objective: The association between serum uric acid (UA) and spontaneous hemorrhagic transformation (HT) has been seldom studied, and the role of UA in spontaneous HT remains unclear. This study aims to investigate the sex-dependent association between UA and spontaneous HT in patients with ischemic stroke Method: We retrospectively included patients with ischemic stroke in a tertiary academic hospital between December 2016 to May 2020. Patients were included if they presented within 24 hours after the onset of symptoms and they did not receive reperfusion therapy. Spontaneous HT was determined by independent evaluation of neuroimaging by three trained neurologists who were blinded to clinical data. Univariate analysis was performed to identify factors related to spontaneous HT. Four logistic regression models were established to adjust each factor and assess the association between UA and spontaneous HT. Results: A total of 769 patients were enrolled (64.6% were males, and 3.9% had HT). After adjusting the confounders with P < 0.05 (model A) in the univariate analysis, the ratio of UA and its interquartile range (RUI) was independently associated with spontaneous HT in males (OR: 1.85; 95%CI: 1.07–3.19; P = 0.028) but not in females (OR: 1.39; 95%CI: 0.28–6.82; P = 0.685). In models B–D, the results remain consistent with model A after adjustment for other potential confounders. Conclusions: Higher serum UA was independently associated with higher occurrence of spontaneous HT in male patients who were admitted within 24h after stroke onset without receiving reperfusion therapy.